2005
DOI: 10.1002/dmrr.576
|View full text |Cite
|
Sign up to set email alerts
|

Effect of antiretroviral agents on carbohydrate metabolism in HIV‐1 infected pregnant women

Abstract: An association was detected between the use of PI and the development of carbohydrate intolerance during pregnancy. The antiretroviral agents had no deleterious effects on perinatal prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Eight per cent of the whole group developed GDM (25% in the HAART/PI group) [25]. Another prospective study analysed the area under the glycaemia curve (AUC) over a period of 120 min between the 33rd and 38th week of gestation on 57 pregnant women [26]. While an increase in the AUC along pregnancy was observed, this increase was significant only in the population receiving HAART therapy, indicating that PI was the likely cause of the glucose intolerance [26].…”
Section: Discussionmentioning
confidence: 99%
“…Eight per cent of the whole group developed GDM (25% in the HAART/PI group) [25]. Another prospective study analysed the area under the glycaemia curve (AUC) over a period of 120 min between the 33rd and 38th week of gestation on 57 pregnant women [26]. While an increase in the AUC along pregnancy was observed, this increase was significant only in the population receiving HAART therapy, indicating that PI was the likely cause of the glucose intolerance [26].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the PACTG 316 study revealed an increased risk of gestational diabetes mellitus in women receiving PI-based HAART before or early in pregnancy 67. Prospective studies have reported similar results 68,69. However, other authors have found no association between PI use and glucose intolerance in either retrospective studies45,70 or larger prospective trials 71…”
Section: Gestational Diabetes Mellitusmentioning
confidence: 97%
“…The inconsistencies of the available results do not permit an analysis of whether HIV increases or decreases the rate of preeclampsia and how ARV therapy affects this rate [97]. Some prospective studies have reported an increased risk of gestational diabetes mellitus in women receiving PI-based HAART before or early in pregnancy [98][99][100], but other authors have found no association between PI use and glucose intolerance [101,102,51]. Further investigations are needed to assess the association between ART and gestational diabetes mellitus, and a close monitoring of glucose level is recommended.…”
Section: Protease Inhibitormentioning
confidence: 99%